2016
DOI: 10.1038/srep20043
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the cytoskeleton in human cells in space proved by life-cell imaging

Abstract: Microgravity induces changes in the cytoskeleton. This might have an impact on cells and organs of humans in space. Unfortunately, studies of cytoskeletal changes in microgravity reported so far are obligatorily based on the analysis of fixed cells exposed to microgravity during a parabolic flight campaign (PFC). This study focuses on the development of a compact fluorescence microscope (FLUMIAS) for fast live-cell imaging under real microgravity. It demonstrates the application of the instrument for on-board … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
123
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(135 citation statements)
references
References 64 publications
10
123
0
2
Order By: Relevance
“…The corresponding protein constitutes an insulin receptor substrate [37], and it has been shown that it is involved in the regulation of lamellipodia formation via activation of the WAVE2 protein [38]. Of note, it has recently been observed, that the formation of filopodia and lamellipodia in thyroid cancer cells were affected by the conditions of a TEXUS sounding rocket flight, which also includes vibration during the take-off phase [39]. Some of the identified genes listed in Table 2, if already characterized, were involved in unrelated general metabolic processes in the cell such as regulation of transcription, oxidation and reduction processes, generation of precursor metabolites and energy, mRNA splicing or DNA-templated transcription.…”
Section: Discussionmentioning
confidence: 99%
“…The corresponding protein constitutes an insulin receptor substrate [37], and it has been shown that it is involved in the regulation of lamellipodia formation via activation of the WAVE2 protein [38]. Of note, it has recently been observed, that the formation of filopodia and lamellipodia in thyroid cancer cells were affected by the conditions of a TEXUS sounding rocket flight, which also includes vibration during the take-off phase [39]. Some of the identified genes listed in Table 2, if already characterized, were involved in unrelated general metabolic processes in the cell such as regulation of transcription, oxidation and reduction processes, generation of precursor metabolites and energy, mRNA splicing or DNA-templated transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Gravitational alterations influence endothelial cell (EC) proliferation, differentiation, signaling, gene expression, surface adhesion molecules, extracellular matrix proteins expression, and cause significant changes in cytoskeletal polymers2345678910.…”
mentioning
confidence: 99%
“…Corydon et al 31 proved by life-cell-imaging that significant alterations of the cytoskeleton occurred during microgravity exposure.…”
Section: Discussionmentioning
confidence: 99%